Relevance and limitations of arc furnace casting in welding research. (April 2015) - Valiente Bermejo, M A.; Zhang, Z.
<x content-type="archive" xml:space="preserve">Abstract</x> The arc furnace melting technique is widely used for positive material identification in the industry of welding consumable manufacturing. It is also a convenient method for sample preparations of various pre-design chemical compositions for investigations on solidification, phase transformation and microstructure of different alloys. However, up to now, welding research works using the arc furnace melting technique did not report to follow any international standard. This is the first time that an international standard involving arc furnace casting is discussed and evaluated to be applied in the welding research field. In this paper, the specimens obtained with the ASTM E1306-94 standard are assessed, and some suggestions are proposed for modification and improvement of the standard, like adding some intermediate steps including the turning over of the specimen and an extra melting. By adopting those proposals in the procedure, cast samples with complete melting and chemical composition homogeneity were achieved.